1999
DOI: 10.1177/101269099034003005
|View full text |Cite
|
Sign up to set email alerts
|

Some Contradictions and Tensions in Elite Sportsmen's Attitudes Towards Their Bodies

Abstract: This article examines some tensions related to how male bodybuilders, ski jumpers, and soccer players view their bodies. Both ski jumpers and soccer players displayed a functional orientation toward their bodies, while the ski jumpers strove for a thin and light body that would improve the length of their jumps. Soccer players also had somewhat diverse body ideals, as the game requires different skills. Bodybuilders were primarily concerned with appearance, especially size. There also was an association betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 13 publications
4
31
0
Order By: Relevance
“…Several studies showed changing perceptions of a person's body in relation to the context in which he or she was situated (e.g. Haimovitz, Lansky, & O'Reilly, 1992; Krane, Waldron, Michalenok, & Stile‐Shipley, 2001; Loland, 1999; Russell, 2004). Athletes also seem to measure themselves in relation to the predominant body ideal of their sport, as well as to hegemonic ideals in society at large (Loland, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies showed changing perceptions of a person's body in relation to the context in which he or she was situated (e.g. Haimovitz, Lansky, & O'Reilly, 1992; Krane, Waldron, Michalenok, & Stile‐Shipley, 2001; Loland, 1999; Russell, 2004). Athletes also seem to measure themselves in relation to the predominant body ideal of their sport, as well as to hegemonic ideals in society at large (Loland, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Haimovitz, Lansky, & O'Reilly, 1992; Krane, Waldron, Michalenok, & Stile‐Shipley, 2001; Loland, 1999; Russell, 2004). Athletes also seem to measure themselves in relation to the predominant body ideal of their sport, as well as to hegemonic ideals in society at large (Loland, 1999). Four qualitative studies illustrated that elite male and female athletes reported to have multiple body images, namely, an athletic and a social body image (Follo, 2007; Krane et al, 2001; Loland, 1999; Russell, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Individuals with higher levels of athletic competence show more enhanced self-concept and SE (Kay, Felker, & Varoz, 1972;Marsh et al, 1997;Marsh et al, 1995), and added to this is the psychological reinforcement of social recognition for their performances (Loland, 1999;Webb, Nasco, Riley, & Headrick, 1998). Other researches found that elite athletes presented greater SE than non-elite athletes (Mahoney, 1989;Marsh et al, 1997) and non-athletes (Kamal, et al, 1995;Marsh et al, 1995).…”
Section: Discussionmentioning
confidence: 99%